North Korea and the 'Peace Games': media representations of sport and politics at the 2018 winter Olympics. Issue 1 (2nd January 2022) - English, Peter; Murray, Richard
ABSTRACT: The reopening of the border hotline between North and South Korea started the process for a unified nation marching in the opening ceremony of the 2018 Winter Olympics. The event was described as the 'Peace Games', highlighting the intersection of sport and politics on a global stage. This article examines the representations in media reporting of North Korea at the 2018 Winter Olympics in six regionally and internationally significant nations. There were 660 online articles from six English-language news websites from North Korea, South Korea, Japan, China, the US, and UK dealing with North Korea's return to the global sporting arena. The results provide an understanding of the different narratives applied when reporting on North Korea in sporting contexts, which in this sample also include broader political elements. In this example, even though North Korea's participation in the Winter Olympics was part of a major sporting event, the importance of political concerns and issues was greater compared with sporting achievements in newsmedia representations of the 2018 Winter Olympics.